The Discovery and History of Animal and Human Physiology - Guirad Oth; Yrick John (Journal La Lifesci, 2020)
This study discusses Nucleus, history of the discovery of the cell nucleus Structure and parts of the cell nucleus. All of them is the phisiology of animal and human. The cell nucleus (nucleus) can be defined as an organelle found in eukaryotic cells. Nucleoplasm The nucleoplasm is the liquid that is in the nucleus which is thick and transparent. The cell nucleus has many genes from DNA which are arranged and form structures called chromosomes. The endoplasmic reticulum consists of tubules, vesicles and flattened pockets that occupy the cytoplasmic space. The endoplasmic reticulum is a part of the cell that consists of a membrane system, which has a structure that resembles a multi-layered sac. These sacs are called cisternae.